Examining the effectiveness of self-narrative diary intervention for mental health during the pandemic - Janowicz, Kamil; Soroko, Emilia; Kleka, Paweł; Dolczewski, Michał; Borzyszkowski, Maciej; Borzęcka, Apolonia (Człowiek i Społeczeństwo, 2025)
This study, rooted in narrative psychology, examined the effectiveness of the proactive self-narrative diary intervention for adults’ mental health during the COVID-19 pandemic. Methods: Four hundred twenty-four people aged 18 to 45 were recruited and divided into three groups: ‘narrative’, ‘descriptive’, and ‘control’. On three consecutive days, participants in the ‘narrative’ group were asked to narrate their daily experiences related to the pandemic. Over the same period, people from the ‘descriptive’ group were asked to answer questions related to their daily activities, while the third group did nothing. The effect of the respective interventions on mental health was assessed in three follow-up measurements (taken a day, two weeks, and two months after the end of the intervention). Self-narrative inclination, awareness of narrative identity, and reflexivity were analyzed as factors modifying the effect of the self-diary intervention. Results: The results indicate a significant decrease in mental health problems over time; however, no differences were found between the three groups. Contrary to the hypotheses, none of the above-mentioned factors acted as a moderator to the effectiveness of the intervention. Conclusions. This experiment suggests that the self-diary intervention has no significant impact on a decrease in mental health problems, or an increase in positive mental health. As this finding is contrary to results of other studies, it can be claimed that not all narrative interventions (and not in all situations) are effective.